High Prevalence of Influenza D Virus Infection in Swine, Northern Ireland - Paula Lagan; Ken Lemon (Emerging Infectious Diseases)
We detected influenza D virus in multiple swine herds in Northern Ireland. Whole-genome sequencing showed several circulating genotypes and novel mutations in the receptor-binding site and esterase domains of the hemagglutinin-esterase fusion protein. Transmission routes of influenza D virus to swine remain to be clarified but could be direct or indirect.